2010
DOI: 10.1002/eqe.1037
|View full text |Cite
|
Sign up to set email alerts
|

Seismic resistance capacity of beam–column connections in high‐rise buildings: E‐Defense shaking table test

Abstract: A series of E-Defense shaking table tests are conducted on a large-scale test specimen that represents a high-rise steel building. Two types of connections featuring the connection details commonly used in 1970s, in the early days of high-rise construction in Japan, are adopted: the field-welded connection consisting of welded unreinforced flanges and a bolted web type, and the shop-welded connection in which the flanges and web are all-welded to the column flange in the shop. To examine the seismic capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Researches on collapse assessment have been developed on several respects during last decades. e experiment on the seismic performance of frame structures is the most direct method to study the failure rule, and a large number of experiments have been carried out [2][3][4][5][6][7][8][9][10]. For instance, Zaharia et al tested two full-scale 3-storey RC structures with flat slab under pseudodynamic loading and concluded that the deformations mainly concentrated in the slabcolumn connections and column bases; Bousias et al tested two 2-storey RC structures with one bay in each direction under earthquake loading.…”
Section: Introductionmentioning
confidence: 99%
“…Researches on collapse assessment have been developed on several respects during last decades. e experiment on the seismic performance of frame structures is the most direct method to study the failure rule, and a large number of experiments have been carried out [2][3][4][5][6][7][8][9][10]. For instance, Zaharia et al tested two full-scale 3-storey RC structures with flat slab under pseudodynamic loading and concluded that the deformations mainly concentrated in the slabcolumn connections and column bases; Bousias et al tested two 2-storey RC structures with one bay in each direction under earthquake loading.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the plastic hinge rotation for the same drift accumulates smaller with the MDAD after yielding of beam ends. The beam ends under negative bending yield earlier with the MDAD, but the influence is limited because the allowable plastic hinge rotation at beam ends under negative bending is approximately 1.5 to 2 times larger than those under positive bending [1][2][3][4][5][6].…”
Section: Introduction Of Minimal-disturbance Arm Dampermentioning
confidence: 99%
“…The quasi‐static test, shaking table test, and pseudo‐dynamic test are the three major test methods in earthquake engineering. The shaking table test is the most straightforward method to investigate seismic responses of structures, for example among many others. The pseudo‐dynamic test, invented about 30 years ago, has also gained popularity , and it has now been expanded to a real‐time controlled method, for example .…”
Section: Introductionmentioning
confidence: 99%